2011
DOI: 10.1038/mt.2010.302
|View full text |Cite
|
Sign up to set email alerts
|

Meganuclease-mediated Inhibition of HSV1 Infection in Cultured Cells

Abstract: Herpes simplex virus type 1 (HSV1) is a major health problem. As for most viral diseases, current antiviral treatments are based on the inhibition of viral replication once it has already started. As a consequence, they impair neither the viral cycle at its early stages nor the latent form of the virus, and thus cannot be considered as real preventive treatments. Latent HSV1 virus could be addressed by rare cutting endonucleases, such as meganucleases. With the aim of a proof of concept study, we generated sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 47 publications
5
70
0
Order By: Relevance
“…In addition, viral replication and infection of cultured cells was substantially diminished when HEs were introduced prior to HSV infection at various multiplicities of infection. This study demonstrated that HSV genomes can be mutated following HE exposure, although cellular toxicity was evident with certain engineered HEs (63).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, viral replication and infection of cultured cells was substantially diminished when HEs were introduced prior to HSV infection at various multiplicities of infection. This study demonstrated that HSV genomes can be mutated following HE exposure, although cellular toxicity was evident with certain engineered HEs (63).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Furthermore, the association of DNA binding and cleavage activity within the same protein domain means that alterations in protein structure to facilitate DNA binding can have deleterious effects on the cleavage activity of the HE. Despite these obstacles, there have recently been several impressive achievements in redirecting HEs toward useful targets (7,63,185), and technical advances in HE redesign and targeting are occurring continually (173). Thus, the 3 classes of proteins (ZFNs, HEs, and TALENs) each have unique advantages and disadvantages, and the ideal protein may vary depending on the particular application envisioned.…”
Section: Specific Types Of Cleavage Enzymesmentioning
confidence: 99%
“…Resulting reduced viral gene expression and elimination of the integrated proviral DNA have been demonstrated [26][27][28]34]. HSV antiviral activity has been observed following site-directed cleavage of the episomal DNA using HEs [31,32] and CRISPR/Cas9 endonucleases [33] in cell culture models of infection. In addition, Aubert and colleagues used an adeno-associated viral vector (AAV) to deliver these anti-HSV HEs [32].…”
Section: General Principles Of Using Gene Editing To Disable Viral Rementioning
confidence: 99%
“…Prior studies of the efficacy of endonuclease treatment of herpesviridae infections, however, had significant limitations. It was shown that meganuclease treatment of cell lines could prevent infection by HSV (28), but the effects of previously existing latent infections were not explored. Another study explored latency treatment using a meganuclease combined with an exonuclease in an HSV model system (5).…”
Section: Discussionmentioning
confidence: 99%